Creating an audience: Experiences from the Surinamese slave registers crowdsourcing project. Issue 3 (3rd July 2019) - Van Galen, Cornelis W.
Abstract: Crowdsourcing for research promises great rewards, but it is often hard to get the public involved in such a way that they are willing to spend their time and money on such a project. The Surinamese Slave Registers crowdsourcing project is an attempt to tackle this problem by combining a crowdfunding campaign with the recruitment of volunteers. To get the public interested, we focussed on inclusion, the sense that we worked together to make this history visible, both in our communication and towards volunteers in the transcription phase. This proved to be a successful combination. Within a month we raised the necessary funds and enlisted hundreds of volunteers, who transcribed a dataset including some 70, 000 enslaved persons in little more than three months.